Reproducibility of Retinal Nerve Fiber Layer Thickness Measures Using Eye-Tracking with Spectral-Domain Optical Coherence Tomography in Children with Non-Glaucomatous Optic Neuropathy - Rajjoub, Raneem D. (Am J Ophthalmol, 2014)
PURPOSE: To determine the intra- and intervisit reproducibility of circumpapillary retinal nerve fiber layer (RNFL) thickness measures using eye-tracking assisted spectral domain optical coherence tomography (SD-OCT) in children with nonglaucomatous optic neuropathy. DESIGN: Prospective longitudinal study METHODS: Circumpapillary RNFL thickness measures were acquired with the Spectralis (Heidelberg Engineering) SD-OCT using the eye-tracking feature at two separate study visits. Children with normal and abnormal vision (visual acuity ≥ 0.2 logMAR above normal and or visual field loss) who demonstrated clinical and radiographic stability were enrolled. Intra- and intervisit reproducibility was calculated for the global average and 9 anatomic sectors by calculating the coefficient of variation and intraclass correlation coefficient. RESULTS: Forty-two subjects (median age 8.6 years, range 3.9 -18.2 years) met inclusion criteria and contributed 62 study eyes. Both the abnormal and normal vision cohort demonstrated the lowest intravisit coefficient of variation for the global RNFL thickness. Intervisit reproducibility remained good for those with normal and abnormal vision, although small but statistically significant increases in the coefficient of variation were observed for multiple anatomic sectors in both cohorts. The magnitude of visual acuity loss was significantly associated with the global (β = 0.026, P < .01) and temporal sector coefficient of variation (β = 0.099, P < .01). DISCUSSION: SD-OCT with eye tracking demonstrates highly reproducible RNFL thickness measures. Subjects with vision loss demonstrate greater intra- and intervisit variability than those with normal vision.